The genus Corybas in Vietnam, with two new records - Truong, Vuong Ba (Universidad de Costa Rica, 2020)
An overview of the orchid genus Corybas in Vietnam is presented. It was known to be represented by a single species, C. annamensis. In this article, we report two new records, C. himalaicus, and C. geminigibbus. Detailed descriptions, synonyms, type data, information on ecology and phenology, distribution and color plates are provided for all three species along with the key to their identification. Key Words: Corybas annamensis, Corybas geminigibbus, Corybas himalaicus, Orchidaceae, Orchidoideae